Excavated waste characteristic from Semarang City landfill sites. Part 1: physical characteristic. (March 2019) - Lokahita, B; Abadi, A M; Hutabarat, I N; Sembiring, L A; Andrianingsih, R T; Samudro, G; Huboyo, H S; Aziz, M; Takahashi, F
Abstract: Globally, Landfill is still the most common method for waste disposal. In most developing countries, the landfill has received municipal waste without going through any separation, even intermediate treatment. Landfill sites have become hidden treasure full of resources. Jatibarang Landfill in Semarang City, Indonesia has been operated since 1992 and received 800 tons of waste daily. This research investigates the characteristic of excavated waste from Jatibarang Landfill. Excavation method was used to obtain a sample from the landfill. The sample will be characterized by its composition and size distribution. Organic waste dominated the composition of waste coming to the landfill, but it was altered after decomposition process in the landfill. Most materials were decomposed and only left the inert material as a majority, undecomposable organic and plastic in the second and third place. It shows that landfill play a significant role in waste decomposition, and by that, there is a possibility to recover recyclable materials or produce solid fuel from the residue.